Effects of Non-genetic Factors on First Dry Period in Hariana cattle atorganized farm (Indian Journal of Animal Production and Management, 2025)
Data of 705 Hariana cows, maintained at livestock farm complex, UP Pandit Deen  Dayal Upadhyaya Pashu Chikitsa Vigyan Vishwavidyalaya Evam Go Anusandhan  Sansthan, DUVASU, Mathura, for a period from 1962 and 2024 was collected to  study effect of non-genetic factors on first dry period. The non-genetic factor effects  such as period, season and AFC age group were studied by least-squares analysis. The  differences between two subclasses of each effect were tested by Duncan Multiple  Range Test. Heritability was estimated by paternal half-sib correlation method. First  dry period was 306.6 days, with standard error and standard deviation of 7.34 and  193.7 respectively. The overall least-squares mean for first dry period estimated were  297.54 ± 9.60 days. Season and period of calving had significant effect on first dry  period. AFC had non-significant effect on first dry period. The heritability estimates  for first service period was 0.164. Genetic correlation of first dry period with breeding  efficiency (Wilcox method), breeding efficiency (Tomar method) and age at first  calving was -0.946, -0.968 and 0.212 respectively.
Keywords: first dry period; genetic correlation Hariana cow; heritability; least-squares analysis